37.0k views
5 votes
Through the origin and (-5,4) point slope form, step by step.

User Paulo
by
5.4k points

1 Answer

0 votes

For this case we have that by definition, the point-slope equation is given by:


(y-y_ {0}) = m (x-x_ {0})

Where:

m: It's the slope
m = \frac {y_ {2} -y_ {1}} {x_ {2} -x_ {1}}\\(x_ {1}, y_ {1}) :( 0,0)\\(x_ {2}, y_ {2}): (- 5,4)

Substituting:


m = \frac {4-0} {- 5-0} = - \frac {4} {5}

Thus, the equation is of the form:


(y-y_ {0}) = - \frac {4} {5} (x-x_ {0})

We substitute a point:
(y-0) = - \frac {4} {5} (x-0)\\y = - \frac {4} {5} x

Answer:


y = - \frac {4} {5} x

User Nassif Bourguig
by
5.2k points